Limiting Amino Acids in Practical Diets for California Yellowtail, Seriola lalandi. Issue 6 (December 2014) - Jirsa, Dave O.; Stuart, Kevin R.; Salze, Guillaume P.; Rhodes, Melanie A.; Davis, D. Allen; Drawbridge, Mark A.
Abstract Three trials were run to identify the limiting dietary amino acids in practical, soy‐based formulations for California yellowtail juveniles. In the first trial, four diets were formulated with 20% fish meal and 43% soy protein concentrate. The basal diet was supplemented with methionine, lysine, and taurine (MLT), and each supplement was then individually deleted in three additional diets (LT, MT, and ML). A significant decrease in growth was only seen in fish fed the ML diet. The second and third trials were designed to test graded levels of dietary taurine and methionine, respectively. Dietary taurine ranged from 0.32 to 1.5%, and methionine levels ranged from 0.95 to 1.19% of the diet with constant levels of cysteine (0.73%). While weight gains were considered adequate to detect a dietary amino acid deficiency, there was no significant effect of graded levels of either taurine or methionine on final weights, growth rates, survival, or feed efficiency. In conclusion, the practical diets tested required taurine supplementations, but did not require lysine or methionine supplementation. While these data are insufficient to determine the taurine or methionine requirement of California yellowtail, it provides minimum levels likely to meet these requirements. Additional research is necessary to determine taurine and methionine requirements precisely in this species.